ANALISIS KEBUTUHAN GURU TERHADAP LKPD IPA DI SD NEGERI 1 SUSUT - Ni Wayan Sri Darmayanti; Rini Yanti, Ni Kadek (Jurnal Pendidikan Dasar Rare Pustaka, 2025)
This research aims to examine teachers' needs regarding the development of Science StudentWorksheets (LKPD) at SDN 1 Susut. From the results of interviews with class IV teachers, it wasrevealed that the dominant learning methods used were group discussions and experiments. Thisapproach is considered effective in increasing student understanding, although teachers facechallenges in adapting learning strategies for students with diverse abilities. The teaching materialsused include textbooks, modules and digital media, but teachers state the need for additional teachingmaterials that are simpler and more focused. LKPD is currently used routinely twice a week, especiallyduring experimental activities. The use of LKPD is considered effective in helping students understandscience concepts, but its development is needed to better improve students' science process skills, suchas observation skills, recording data, and using experimental tools. This research emphasizes theimportance of developing more inclusive and adaptive LKPD, which not only supports conceptualunderstanding, but also deepens students' scientific skills at various ability levels. Thus, it is hoped thatbetter LKPD can be an alternative to improve the quality of learning. science, especially in improvingscience skills.